Determinants of Human Immuno Deficiency Virus (HIV) Prevalence in the Central Region of Ghana - Gyaase, Philip; Aanienang, Eugene Kpinee; Mensah, Peggy; Adzordor, Patience; Tweneboah, Samuel Kwame; Amoakoaa, Evelyn Aidoo; Bawammah, Lambon Wisdom; Acheampong, Emmanuel Boateng; Eshun, Emmanuel Kwesi; Sampson, David Ben (Asian Journal of Research in Infectious Diseases, 2024)
Background: A lot of interventions have targeted to reduce exposure to HIV risk factors however HIV continues to affect millions of people. The purpose of the study was to assess the determinants of HIV prevalence in the Central Region of Ghana. Methods: A facility based cross sectional study was conducted in six hospitals in the Central Region from March to July, 2024. Stratified and census sampling techniques were used to select respondents who came for HIV Counseling and Testing (HCT) at the health facilities. A structured questionnaire was used to take data from 423 clients accessing HIV counselling and testing services. Bivariate analysis was used to identify the sociodemographic factors associated with HIV prevalence in the region. Results: Majority of the respondents 416(98.3%) were HIV negative while 7(1.65%) were positive making the prevalence rate in the region to be 1.65%. On the determinants of HIV, the following variables were associated with the HIV prevalence: Age and marital status were statistically significant (p-value <0.001) the rest of the variables were not statistically significant as p-values were above 0.05 significance level. Conclusion: The HIV prevalence rate in the Central Region is lower than the national and global prevalence rates. The factors that were linked to the prevalence of HIV included age and marital of the respondents. The study concludes that though the prevalence of HIV in the region is low the youth and married individuals have contributed to the level of HIV in the region. However measures should still be put in place to eliminate the condition from the region and this will help to achieve the SDG 3.